2017
DOI: 10.3839/jabc.2017.024
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect ofAcer okamotoanumfrom oxidative stress in C6 glial cells

Abstract: Radical scavenging effect and protective activity against oxidative stress of Acer okamotoanum were investigated. A. okamotoanum was extracted with methanol (MeOH) and then fractionated with n-BuOH, ethyl acetate (EtOAc), methylene chloride and n-hexane fractions. The MeOH extract and fractions showed strong 1,1-diphenyl-2-picrylhydrazyl and superoxide radical scavenging activity. Among the MeOH extract and fractions, the EtOAc fraction showed the strongest radical scavenging activity. In addition, total pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Therefore, to extract a large quantity of hydrophilic bioactive compounds, we used MeOH and EtOAc. In addition, we previously reported that the EtOAc fraction from A. okamotoanum has higher in vitro free radical scavenging activities against DPPH and O À 2 and higher total phenolic and flavonoid contents, compared with n-BuOH, methylene chloride and n-hexane fractions, and the crude MeOH extract (Choi et al, 2017a). Furthermore, the EtOAc fraction of A. okamotoanum led to a significant protective effect in oxidative stress-induced C6 glial cells among other extracts and fractions (Choi et al, 2017a).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Therefore, to extract a large quantity of hydrophilic bioactive compounds, we used MeOH and EtOAc. In addition, we previously reported that the EtOAc fraction from A. okamotoanum has higher in vitro free radical scavenging activities against DPPH and O À 2 and higher total phenolic and flavonoid contents, compared with n-BuOH, methylene chloride and n-hexane fractions, and the crude MeOH extract (Choi et al, 2017a). Furthermore, the EtOAc fraction of A. okamotoanum led to a significant protective effect in oxidative stress-induced C6 glial cells among other extracts and fractions (Choi et al, 2017a).…”
Section: Resultsmentioning
confidence: 85%
“…In addition, we previously reported that the EtOAc fraction from A. okamotoanum has higher in vitro free radical scavenging activities against DPPH and O À 2 and higher total phenolic and flavonoid contents, compared with n-BuOH, methylene chloride and n-hexane fractions, and the crude MeOH extract (Choi et al, 2017a). Furthermore, the EtOAc fraction of A. okamotoanum led to a significant protective effect in oxidative stress-induced C6 glial cells among other extracts and fractions (Choi et al, 2017a). The most active compounds from the EtOAc fraction of A. okamotoanum leaves were flavonol glycosides such as quercetin-3-O-b-D-galactopyranoside and quercetin-3-O-a-L-arabinopyranoside (Choi et al, 2017b).…”
Section: Resultsmentioning
confidence: 96%
“…These defense mechanisms against oxidative stress called the anti-oxidation are the mechanism for inhibiting the production or returned to normal levels that the over-produced free radicals at the energy production process in vivo [2]. Reactive oxygen species are produced in the process of stabilizing by taking incomplete electrons generated during the mitochondrial respiratory process from nearby molecules, and types include singlet oxygen ( 1 O 2 ), superoxide (O 2− ), hydroxyl radical (OH), and hydrogen peroxide (H 2 O 2 ) [2,3]. These reactive oxygen species are very unstable and highly reactive, easily react with various biological materials, and attack the polymers in the body, causing irreversible damage to cells and tissues, mutations, and cancer.…”
Section: Introductionmentioning
confidence: 99%
“…It is also known to cause diabetes, brain disease, and cardiovascular disease. Therefore, for the prevention and treatment of many chronic degenerative diseases in which oxidative stress caused by free radicals acts as a risk factor, many studies have been conducted to find antioxidants from natural products with low toxicity and side effects [3].…”
Section: Introductionmentioning
confidence: 99%
“…After three days adaptation, four groups with HFD-and Aβ 25-35 -induced mice were orally administered with EAO (100 mg/kg/day), isoquercitrin (10 mg/kg/day), donepezil (5 mg/kg/day), and CLA (750 mg/kg/day) dissolved in 0.5% carboxymethylcellulose (CMC) for four weeks. The experimental groups were divided into six groups as follows: (1) normal, mice fed with ND, injected saline solution, and orally administered 0.5% CMC; (2) control, mice fed with HFD, injected Aβ [25][26][27][28][29][30][31][32][33][34][35] , and orally administered 0.5% CMC; (3) AO, mice fed with HFD, injected Aβ 25-35 , and orally administered EAO; (4) IQ, mice fed with HFD, injected Aβ [25][26][27][28][29][30][31][32][33][34][35] , and orally administered isoquercitrin; (5) DO, mice fed with HFD, injected Aβ [25][26][27][28][29][30][31][32][33][34][35] , and orally administered donepezil; (6) CLA, mice fed with HFD, injected Aβ 25-35 , and orally administered CLA. Food intakes and body weight were consistently measured every day during the experiment.…”
Section: Introductionmentioning
confidence: 99%